Best practices for teaching science : what award-winning classroom teachers do - Stone, Randi (Thousand Oaks, CA : Corwin Press)
Expeditionary learning receives prestigious toyota tapestry grant: Project Dracula / Peter M. Menthe -- Less is more-- really / Stanley A. Wawrzyniak -- More than just rockets / Douglas L. Bailer -- Gravity / Carol J. Skousen -- Making microbes fun / Jason E. Hughes -- Building our curriculum as we build a straw-bale greenhouse / Sally Ogilvie -- Real-world science engagement / Kimberly Reining-Gray -- A method for inquiry science / Mark Goldner -- Using technology and music to motivate science students / Brenda Zabel -- The power of building a positive classroom climate / Cindy Corlett -- Mission possible / Pam Roller -- Robots: from science fiction to science fact / Lindsey Prentice -- A different kind of service / Deborah Perryman -- Environmental studies enhance middle school education / Nancy Elliott -- An independent student research program implemented in a rural Michigan community / Jeff Shull -- An inquiry-based, student-centered approach / Jeff Shull -- One very special evening of science / Frieda Taylor Aiken.